Alternative Configuration in Earthmoving Operations for Minimizing Unit Emissions and Unit Cost - Mustaffa, Nur Kamaliah (International Journal of Integrated Engineering, 2020)
Earthmoving operations commonly utilize a large range of equipment that generates a considerable amount of greenhouse gas (GHG) emissions. Identifying effective methods to improve the operational efficiency of equipment is important in order to reduce emissions in earthmoving operations. With most of the current efforts in construction have primarily been focused on improving performance in terms of production, cost and duration, this study examines the alternative configuration of earthmoving operations in terms of least unit emissions and minimum unit cost. The Monte Carlo simulation model in conjunction with field-measurement data are used to estimate and compare the optimum fleet size, minimum unit emissions and minimum unit cost for excavator-truck operation. It is demonstrated that by minimizing waiting time through double-sided loading practice leads to a decrease in emissions per production and cost per production in earthmoving operations. The results indicate the most environmentally friendly way to configure and manage earthmoving operations and will be of interest to the contractor who is looking to reduce construction emissions on site.